Sustainable practices in the cocoa value chain: a systematic literature review - Mónica María Olarte Libreros; Carlos Mario Muñoz Maya (Tendencias)
Introduction: This article identifies sustainable practices in cocoa farming, in the new scenarios of voluntary certifications and the circular economy. Objective: The main objective is to analyse and synthesise the sustainable strategies and approaches implemented in the cocoa value chain. Methodology: The PRISMA protocol was applied, which was used to define the 45 documents from the Scopus and Web of Science databases that were part of the systematic literature review with a publication range between 2016 and 2024. Results: Agroforestry widely emerges as the main production strategy to minimise the overall environmental and socioeconomic impacts associated with cocoa production. Sustainable practices focus on production and governance aspects. Conclusions: In relation to sustainability standards, there is a transition from voluntary approaches to stricter regulations within the value chain that force cocoa producers to adopt sustainable investment decisions, which not only comply with environmental and labour standards, but also generate long-term benefits.